Dendrimers, Dendrons, and the Dendritic State: Reflection on the Last Decade with Expected New Roles in Pharma, Medicine, and the Life Sciences - Donald A. Tomalia (Pharmaceutics, 2024)
This perspective begins with an overview of the major impact that the dendron, dendrimer, and dendritic state (DDDS) discovery has made on traditional polymer science. The entire DDDS technology is underpinned by an unprecedented new polymerization strategy referred to as step-growth, amplification-controlled polymerization (SGACP). This new SGACP paradigm allows for routine polymerization of common monomers and organic materials into precise monodispersed, dendritic macromolecules (i.e., dendrons/dendrimers) with nanoscale sizes and structure-controlled features that match and rival discrete in vivo biopolymers such as proteins and nucleic acids (i.e., DNA, siRNA, mRNA, etc.). These dendritic architectures exhibit unprecedented new intrinsic properties widely recognized to define a new fourth major polymer architecture class, namely: Category (IV): dendrons, dendrimers, and random hyperbranched polymers after traditional categories: (I) linear, (II) cross-linked, and (III) simple-branched types. Historical confusion over the first examples of the structure confirmed and verified cascade, dendron, dendrimer, and arborol syntheses, while associated misuse of accepted dendritic terminology is also reviewed and clarified. The importance of classifying all dendrons and dendrimers based on branch cell symmetry and the significant role of critical nanoscale-design parameters (CNDPs) for optimizing dendritic products for pharma/nanomedicine applications with a focus on enhancing stealth, non-complement activation properties is presented. This is followed by an overview of the extraordinary growth observed for amphiphilic dendron/dendrimer syntheses and their self-assembly into dendritic supramolecular assemblies, as well as many unique applications demonstrated in pharma and nanomedicine, especially involving siRNA delivery and mRNA vaccine development. This perspective is concluded with optimistic expectations predicted for new dendron and dendrimer application roles in pharma, nanomedicine, and life sciences.